The Effect Of Physical Treatment and Concentration Of KNO3 Against The Breakdown Of Dormancy and Growth Seeds Of Bile Plants (Caesalpinia Bonduc. L ) - Nurul Rosidah; Fiana Podesta; Dwi Fitriani; Ririn Harini; Suryadi Suryadi (Nabatia, 2023)
This study aims to determine the effect of physical treatment and concentration of KNO3 on the breakdown of dormancy and seed growth of bile plants (Caesalpinia bonduc L). The design used is RAL Factorial with 2 factors, namely the first factor Physical treatment (F): F0 (Control), F1 (sanding), F2 (wounding), while the second factor KNO3 concentration (K): K0 (Control), K1 (0.1%), K2 (0.2%), K3 (0.3%) Each treatment is repeated 3 times. The results of the data were analyzed using fingerprint analysis (ANOVA) and if the difference was marked, Duncan's Multiple Range Test (DMRT) was carried out at 5%. The results showed the interaction of physical treatment and KNO3 concentration on Growing Percentage, Plant Height 2, 6, 8, 10 MST and Root Length. and In physical treatment has a very noticeable effect on Growing speed, growing percentage, Plant height 2, 4, 6, 8, 10 MST, Number of leaves 4, 6, 8, 10 MST, Root length, as well as on KNO3 b Concentration Treatment It has a very real effect on Growing Speed, Growing Percentage, Plant Height, 2, 4, 6, 8, 10 MST, Leaf count 4 MST, Root length and has a significant effect on leaf count 6, 8, 10 MST.